Impact of educational institutions on the development of printing press in Malaya: 1880-1930 - Awang Damit, Noraidah; Akhmetova, Elmira (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2017)
This article reviews the role of educational institutions in the development of printing press industry in Malaya from the mid of the nineteenth to the early twentieth centuries. The main focus of the paper is to investigate the effects of educational institutions on the emergence of printing press companies. The paper suggests that, although the printing press was already present in Malaya in the early nineteenth century, there were no companies yet being interested to produce local newspapers and periodicals until the arrival of the London Missionary Society as well as other European educational and missionary activities at Malaya. Their arrival, as the paper suggests, coincided with the increased role of education, which is evident in the rapid growth of educational institutions. The major finding of the paper is that the establishment of the printing press in Malaya was influenced by both, the growth in educational institutions and the European intervention, even though the former should be considered as the main factor.